Standard of Physical Education in Pakistan as Compare to U.S.A. (Global Journal of Human-Social Science, 2014)
This research article is intended to compare the standard of physical education in Pakistan with U.S.A. The basic purpose of study was to investigate the flaws and their causes in the field of physical education in Pakistan. The physical education program is compared at the level of facilities i.e. institutes, faculty, laboratories and equipments, funding and society awareness. The assertion of this premise is established by data collecting through as self administered questionnaire with a sample of 250 people and also through interview of higher authorities of physical education program in especially Pakistan and U.S.A. The findings of this study indicate that the standard of physical education is worse in Pakistan due to unavailability of institutes, highly qualified staff, latest equipments and social awareness; where as the situation in U.S.A is vice versa.